2002
DOI: 10.1179/016164102101200915
|View full text |Cite
|
Sign up to set email alerts
|

Caspase inhibitors reduce the apoptotic but not necrotic component of kainate injury in primary murine cortical neuronal cultures

Abstract: Excitotoxicity has been demonstrated to play a major role in ischemic neuronal injury. While the necrotic component of excitotoxicity has been well demonstrated, apoptosis has also been shown to play a role. We sought to quantitate and modulate the apoptotic component of kainate-induced injury. Experiments were performed in mouse primary cortical neuronal cultures after three or 10 days in vitro. Cell death was assessed by Hoechst/propidium iodide staining and cell counting. Apoptosis was further confirmed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Our results show that early-culture microglia are more vulnerable to stresses that simulate ischemia as well as to induction of apoptosis by loss of growth factors (SD). This decrease in vulnerability to injury with age in culture is similar to the response of oligodendrocytes (9) and contrasts with findings for neurons and astrocytes (18,19).…”
Section: Discussioncontrasting
confidence: 46%
“…Our results show that early-culture microglia are more vulnerable to stresses that simulate ischemia as well as to induction of apoptosis by loss of growth factors (SD). This decrease in vulnerability to injury with age in culture is similar to the response of oligodendrocytes (9) and contrasts with findings for neurons and astrocytes (18,19).…”
Section: Discussioncontrasting
confidence: 46%
“…It has been suggested that de novo protein synthesis may be essential for activation of caspase-regulated apoptosis. 32,55,56 Consistent with the studies using caspase inhibitors, inhibition of protein synthesis did not protect cortical neurons from the neurotoxic effects of anandamide. In contrast, parallel studies using treatment with etoposide, a classical method of inducing caspase-3-mediated neuronal apoptosis, showed cycloheximide blockade of apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…However in adult animals, most pathologists have been taught that the classic “dead red” neuron, which is the most common morphologic manifestation of neuronal death, is a necrotic cell (Figure 19A) (Morgan et al 2004). During the past 10 – 15 years a substantial amount of research has been done to characterize the mechanism of cell death resulting from various toxicants (e.g., domoic or kainic acid, TMT, lead) and pathologic conditions (e.g., seizures, cortical trauma), and it is becoming increasingly apparent that both necrosis and apoptosis can occur in response to the same type of insult, and with similar morphological features with H&E staining (Figure 19B) (Ettcheto et al 2015; Giordano et al 2008; Glassford et al 2002; Krajewska et al 2011; Martin et al 1998; Wang et al 2005; Zhang and Zhu 2011). Morphologically, one may have a sense for which process predominates based on cellular features (Figure 19C), the extent of neuronal loss/death, the amount of tissue damage, and the glial/inflammatory response, but it may be difficult to discern with certainty in most cases without special stains.…”
Section: Organ Specific Examplesmentioning
confidence: 99%